Can latitudes become forms? Unveiling purpose in higher education practice. Issue 1 (1st March 2016) - Bastos, Flávia M. C.
My praxis as teacher/scholar and the journey that led me here is marked by the political dimensions of education and visual art. For me, this relationship between education and politics is rooted in the Brazilian context of the mid-1960s, a time of great upheaval. Then and there, education and art provided strategies of resistance, with the arts articulating protest in veiled and codified language and transformative education methodologies providing tools to displace oligarchical assumptions about knowledge and society. This manuscript explores the motivations shaping my higher education work and its trajectory from my formative experiences in Brazil, and my professional training in the United States, to a global career.